2022
DOI: 10.1111/jan.15435
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge and confidence in recognizing and managing patients with sepsis: A multi‐site cross‐sectional study

Abstract: Aims (1) To examine registered nurses' knowledge and confidence in recognizing and managing to patients with sepsis and (2) identify nurse and workplace factors that influence their knowledge on sepsis. Design A multi‐site, cross‐sectional survey. Methods An online survey was developed and content validated. Data was collected from registered nurses working in the inpatient wards and emergency departments of three hospitals of a single healthcare cluster in Singapore during August 2021. Statistical analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In Singapore nurses possessed moderate levels of knowledge about sepsis and confidence in recognizing and responding to patients with sepsis. Only 52.0% could correctly define sepsis [ 23 ]. These study shows that knowledge of nurses in some areas of infectious diseases is not adequate.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore nurses possessed moderate levels of knowledge about sepsis and confidence in recognizing and responding to patients with sepsis. Only 52.0% could correctly define sepsis [ 23 ]. These study shows that knowledge of nurses in some areas of infectious diseases is not adequate.…”
Section: Discussionmentioning
confidence: 99%
“…In one study conducted in Japan, a great difference was found between actual practice and awareness among stroke care unit nurses [ 15 ]. In an online survey reported in Singapore, it was found that nurses with higher education or experience in an emergency got more knowledge scores [ 16 ]. A similar result was found in a cross-sectional study in Ethiopia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A descriptive study conducted to evaluate nurses' knowledge of patients in shock, revealed that, more than half of the study participants had adequate understanding of trauma patients in shock [75]. Further research to evaluate nurses' shock knowledge revealed that nurses had sufficient shock knowledge [76].…”
Section: Knowledge Of Early Symptoms Of Haemorrhagic Shock By Nursesmentioning
confidence: 95%